Stochastic heating of electrons by electromagnetic waves - Ognivenko, V.V. (Вопросы атомной науки и техники, 2000)
In the present paper the nonlinear dynamics of electrons motion in the fields of two combinational waves or in the fields of one combinational wave and a longitudinal wave is considered. The mechanism of electrons energy grows under an overlap of two nonlinear resonances is investigated and upper limit of the electron energy is determined.